The evolution of biological theories: explaining the success of Mendelian genetics, Darwin’s Theory of natural selection and their synthesis - Elliott, Mats (Department of Philosophy, 2020)
Darwin’s theory of natural selection was not widely accepted in the biological community until its synthesis with Mendelian genetics. I investigate the history of both sciences, with the aim discovering why Mendelian genetics and the synthesis were scientifically successful. One possible explanation for this is given by constructivism, the view that developments in science are decided not by rational reasons, but by contingent factors. A sophisticated version of this view is defended by Gregory Radick, who argues that Weldonian biometry, a rival theory of inheritance, could have supplanted Mendelism. For Radick, the success of Mendelism and the corresponding decline of biometry can be explained by historical circumstances, such as Weldon’s untimely death and his inability to recruit talented students. Another popular philosophical explanation of scientific developments is scientific realism, whose proponents argue that scientific success can be explained by the truth of scientific theories. More sophisticated versions of realism, such as Weisberg’s, take the routine scientific distortion of truth (idealization) into account. I argue from the history of genetics that neither constructivism nor realism, sophisticated or otherwise, can help us understand the success of Mendelian genetics. Instead, I argue that there were rational reasons in favor of Mendelian genetics, even if it was not a true theory of inheritance. I further conclude that the synthesis was successful because Mendelian genetics theoretically enriched Darwin’s theory of natural selection. This enrichment solved serious empirical and conceptual problems for Darwin’s theory, showing that we can also understand the success of the synthesis without appeal to broad realist or constructivist views.